Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10741-011-9292-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of heart failure self-care: a systematic literature review

Abstract: Self-care is an important aspect of heart failure (HF) management. Information on the determinants of self-care is necessary for the development of self-care promotion interventions. HF self-care includes self-care management, self-care maintenance, sodium, fluid and alcohol intake restriction, physical activity, smoking cessation, monitoring signs and symptoms and keeping follow-up appointments. To assess the evidence regarding presumed determinants of HF self-care and make recommendations for interventions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 60 publications
(108 reference statements)
2
63
0
1
Order By: Relevance
“…From the current review, several psychological barriers and facilitators of HF self-care have been identified beyond other sociodemographic and clinical determinants (8,11), as we have illustrated in a conceptual model (Fig. 5).…”
Section: Discussionmentioning
confidence: 88%
“…From the current review, several psychological barriers and facilitators of HF self-care have been identified beyond other sociodemographic and clinical determinants (8,11), as we have illustrated in a conceptual model (Fig. 5).…”
Section: Discussionmentioning
confidence: 88%
“…Previously published reviews offer a more general account of self-care in HF or the experience of living with HF [38][39][40][41][42][43], rather than care seeking decisions specifically, or do not go beyond summarizing what is already reported in the literature [44].…”
Section: Figmentioning
confidence: 99%
“…Several studies identify barriers to performing recommended heart failure self-care (McEntee et al, 2009; Oosterom-Calo et al, 2012; Siabani et al, 2013; Zavertnik, 2014). Most of the studied barriers are patient-related factors such as age, lack of knowledge, and low self-efficacy (Oosterom-Calo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%